How do you solve #-5(m-1)+3(2m-1)=8# using the distributive property?

Answer 1

See the entire solution process below:

First, expand both terms in parenthesis on the left side of the equation by multiplying each term within the parenthesis by the term outside the parenthesis:

#color(red)(-5)(m - 1) + color(blue)(3)(2m - 1) = 8#
#(color(red)(-5) * m) + (color(red)(-5) * -1) + (color(blue)(3) * 2m) - (color(blue)(3) * 1) = 8#
#-5m + 5 + 6m - 3 = 8#

Next, group and combine like terms on the left side of the equation:

#6m - 5m + 5 - 3 = 8#
#(6 - 5)m + (5 - 3) = 8#
#1m + 2 = 8#
#m + 2 = 8#
Now, subtract #color(red)(2)# from each side of the equation to solve for #m# while keeping the equation balanced:
#m + 2 - color(red)(2) = 8 - color(red)(2)#
#m + 0 = 6#
#m = 6#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To solve the equation -5(m-1)+3(2m-1)=8 using the distributive property:

-5(m-1) = -5m + 5 3(2m-1) = 6m - 3

Combine like terms: -5m + 5 + 6m - 3 = 8 -5m + 6m + 5 - 3 = 8 m + 2 = 8

Subtract 2 from both sides: m = 8 - 2 m = 6

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

To solve the equation -5(m - 1) + 3(2m - 1) = 8 using the distributive property, we first apply the distributive property to each term within the parentheses:

-5(m - 1) = -5m + 5 3(2m - 1) = 6m - 3

Now, we substitute these expressions back into the original equation:

(-5m + 5) + (6m - 3) = 8

Next, we combine like terms:

-5m + 6m + 5 - 3 = 8

Now, we simplify the expression:

-5m + 6m + 2 = 8

Now, we combine like terms again:

(6m - 5m) + 2 = 8

m + 2 = 8

To isolate the variable m, we subtract 2 from both sides of the equation:

m = 8 - 2

m = 6

Therefore, the solution to the equation -5(m - 1) + 3(2m - 1) = 8 is m = 6.

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7